Projected shifts in coffee production and sustainability due to climate changes - Rahn, Eric; Bunn, Christian; Craparo, Alessandro (Elsevier, 2025)
Climate change has emerged as a key concern for coffee production. An ever-growing body of research demonstrates potential impacts at all scales from plant to sector. We show that the literature for the most part frames climate change as a geospatial phenomenon. Global and regional projections robustly show an overall reduction in potential area climatically suitable for coffee, with shifts towards higher elevations and relative winners and losers. Research which looked at other dimensions of climate change, such as the potential impacts of climate variability and climate trends by using detailed survey data and statistical models, show a more diverse, albeit mixed, image of shifts in coffee production. However, there are several limitations in used methodologies and the way the results are communicated, which require increased attention to advance scientific framing of potential climate change impacts in the different coffee origins to better guide adaptation planning. We suggest that future research would benefit from a social-ecological resilience lens with greater integration of empirical analyses and process-based modelling approaches. Future responses to climate change will initially be less of a geographical shift but rather major changes to agronomic management, producer’s economic strategies and physical and informational fluxes. Such a framing would better capture the complexity of climate impacts and consequently the ability to support adaptation planning.